Neuroinflammation associated with proviral DNA persists in the brain of virally suppressed people with HIV - Byrnes, Sarah J.; Jamal Eddine, Janna; Zhou, Jingling; Chalmers, Emily; Wanicek, Emma; Osman, Narin; Jenkins, Trisha A.; Roche, Michael; Brew, Bruce J.; Estes, Jacob D.; Angelovich, Thomas A.; Churchill, Melissa J. (Frontiers in Immunology, 2025)
Despite viral suppression with antiretroviral therapy (ART), people with HIV (PWH) continue to exhibit brain pathology, and ~20% of individuals develop HIV-associated neurocognitive disorders. However, the state of cellular activation in the brain of virally suppressed (VS) PWH and the impact of local viral reservoirs on cellular activation are unclear. Using multiplex immunofluorescence imaging, here, we demonstrate that the frontal cortex brain tissue from both non-virally suppressed (nVS; n=17) and VS PWH (n=18) have higher frequencies of astrocytes and myeloid cells expressing interferon-inducible Mx-1 and proinflammatory TNFα relative to HIV-seronegative individuals (p<0.05 for all). The frequency of TGF-β1+ cells were also elevated in the brain tissue from both nVS and VS PWH, which may support active immunoregulatory responses despite ART. Importantly, the frequency of Mx1+ myeloid cells correlated with levels of total HIV DNA and intact and 5′ defective HIV proviral DNA (p<0.05 for all) in the brain of VS PWH. These findings demonstrate that cell activation persists in the brain of VS PWH and is associated with HIV DNA in the brain, which may contribute to neuropathology.